2021
DOI: 10.1021/acsami.1c07400
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs as a New Platform for Tuning the Biosynthesis of Silver Nanoparticles for Enhanced Material and Functional Properties

Abstract: Genetic engineering of nanoparticle biosynthesis in bacteria could help facilitate the production of nanoparticles with enhanced or desired properties. However, this process remains limited due to the lack of mechanistic knowledge regarding specific enzymes and other key biological factors. Herein, we report on the ability of small noncoding RNAs (sRNAs) to affect silver nanoparticle (AgNP) biosynthesis using the supernatant from the bacterium Deinococcus radiodurans. Deletion strains of 12 sRNAs potentially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…In the past, extensive studies have been conducted to understand the mechanism of the resistance of D. radiodurans to oxidative stresses, most of which mainly focused on gene regulation, protein functions, and sRNA regulations ( 38 , 39 , 46 , 50 52 ). Our previous work has revealed that ionizing radiation can cause a significantly increased 8-oxoG-RNA concentration in D. radiodurans ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, extensive studies have been conducted to understand the mechanism of the resistance of D. radiodurans to oxidative stresses, most of which mainly focused on gene regulation, protein functions, and sRNA regulations ( 38 , 39 , 46 , 50 52 ). Our previous work has revealed that ionizing radiation can cause a significantly increased 8-oxoG-RNA concentration in D. radiodurans ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic nanomaterials with direct bactericidal effects include calcium silicate (CaSi) [15,21], silver (Ag) [22,23], copper (Cu) [24,25], and gold (Au) NPs [17,18]. Among the inorganic nanomaterials, Ag NPs have been one of the most widely used antimicrobial materials due to their broad-spectrum antibacterial capacity and low propensity to engender drug resistance [18].…”
Section: The Development Of Organic Inorganic and Hybrid Nps For Infectious Diseasesmentioning
confidence: 99%
“…Among the inorganic nanomaterials, Ag NPs have been one of the most widely used antimicrobial materials due to their broad-spectrum antibacterial capacity and low propensity to engender drug resistance [18]. Ag NPs had a good antimicrobial effect in both gram-positive and gram-negative bacteria, for example methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), Pseudomonas aeruginosa, and Klebsiella pneumoniae [18,22,23]. Au NPs have been shown to decrease the effect of lipopolysaccharide (LPS), an important toxin in gram-negative bacteria that causes fulminant immune responses through its effect on dendritic cells and immune reactions [26].…”
Section: The Development Of Organic Inorganic and Hybrid Nps For Infectious Diseasesmentioning
confidence: 99%
“…Rr bacteria resist osmotic and acid stress temperature variation and have a pool of enzymes, making them a suitable candidate in fermentation biotechnology. In addition, Rr bacteria exhibit tolerance to heavy metals, playing a crucial role in the bioremediation of pollutants and the biodegradation of radioactive and radionucleotide waste ( Luo et al, 2014 ; Beblo-Vranesevic et al, 2017 ; Chen et al, 2021 ; Nayak et al, 2021 ; Kumar et al, 2022 ). Furthermore, Rr bacteria produce various extremolytes, and their potential sunscreen ability is already commercialized and effectively utilized by skincare industries ( Mendes-Silva et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%